ETNOMATEMATIKA: EKSPLORASI KONSEP GEOMETRI DALAM ANYAMAN TRADISIONAL MADURA - Ukhti Raudhatul Jannah; Siti Nur Maulidia; Ayunda Novita Indah Lestari; Moh Muhlis (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2025)
This study aims to explore the potential of traditional Madura weaving to visualize geometric concepts in mathematics learning. This study applies a qualitative method with a descriptive approach, using literature study as a research method to determine the potential of ethnomathematics related to geometric concepts in traditional Madura weaving. Data analysis in this study was carried out in three stages, namely data reduction, data presentation, and conclusion drawing. Based on the results obtained from the research, it is known that there are elements of geometric concepts in traditional Madurese weaving, namely besek, caping, and fish baskets, including flat shapes and spatial shapes. The findings of this study can be used as a reference in implementing ethnomathematics-focused learning in the classroom, so that the teaching and learning process is more relevant and closer to the lives of students